A Fine Line Painkillers and Pleasure in the Age of Anxiety - Dertadian, George C. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Are painkillers mundane medications safe for use to ease human suffering? Or are they drugs of abuse that cause addiction and death? Do they ameliorate pain, or do they cause it? This book explores growing interest among medical practitioners media outlets about the 'misuse' or 'abuse' of pharmaceutical pain medications. It contextualizes these emerging discourses of pharmaceutical 'abuse' within the social and political histories from which they have emerged by exploring the role of pleasure and pain in shaping individualized modes of medication consumption in a neoliberal age of anxiety. The book is divided into two parts: the first addresses the discursive construction of painkiller (ab)use as articulated in research and policy accounts; the second part provides an empirical investigation that draws on the lived experience of those who engage in non-medical consumption. This book argues that, contrary to the stereotype of the 'seductive' drug that coaxes its user into a life of dysfunction, there appears to be an intimate relationship between the motivations of pleasure seeking, health practice and productive citizenship among people who use painkillers for non-medical reasons.